Hydrogen production by Rhodobacter sphaeroides DSM 158 under intense irradiation. (January 2015) - Krujatz, Felix; Härtel, Paul; Helbig, Karsten; Haufe, Nora; Thierfelder, Simone; Bley, Thomas; Weber, Jost
Graphical abstract: Highlights: R. sphaeroides DSM158 was cultivated in an irradiated stirred tank reactor. Intense irradiation caused high rH2 and dry weight of R. sphaeroides DSM158. I 0 had a greater influence on rH2 compared to P 0 / V L . Intense irradiation conditions were successfully transferred to continuous mode. Abstract: To identify optimal hydrogen production conditions using growing cultures of Rhodobacter sphaeroides DSM 158 the effects of varying the reactor's volumetric power input (0.01–1.4 kW m −3 ) and irradiation intensity (5–2500 W m −2 ) were investigated in batch and continuous production modes. Irradiation intensity had a greater effect on hydrogen production than volumetric power input. Hydrogen production and photofermentative biomass formation were maximized by irradiation at 2250 W m −2 with a volumetric power input of 0.55 kW m −3 . The bacterial dry weight (2.64 g L −1 ) and rate of hydrogen production (195 mL L −1  h −1 ) achieved under these conditions were greater than any that have previously been reported for batch-mode hydrogen production by R. sphaeroides . Continuous mode experiments ( D  = 0.1 h −1 ) yielded a bacterial dry weight, hydrogen production rate, productivity and hydrogen yield of 2.35 ± 0.18 g L −1, 165 ± 6.2 mL L −1  h −1, 3.96 L L −1  d −1 and 36.6%, respectively.